TEORI TRANSFER DAN TEORI INTERFERENSI DALAM PEMEROLEHAN BAHASA KEDUA ATAU BAHASA TARGET - Anik Cahyaning Rahayu (Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. The Prosess of transfer and interference will always follow the second language acquisition. This happens especially at the beginning of acquisition process. Transfer and interference relate to the influence of the first or previous language to the second or target language. Transfer is divided into positive and negative transfer. Positive transfer will happen it there are similarities between the first and the second language. This first will support the process of the second language acquisition. On the other wny around if there are differences between the structure of the first language and the structure of the second one, the negative transfer will happen. This kind of transfer is called interference. Interference will interfere or not support the process of the second language acquisition.Â Key words: Tranfer, interference, the second language acquisition